PENGARUH LAYANAN PAYLATER, GAYA HIDUP, LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN GEN Z - Dewi, Popi Melani; A. Khoirul Anam (MANAJEMEN DEWANTARA, 2026)
The development of digital financial services such as PayLater is increasingly popular among Generation Z, including students, due to its ease of access, fast processing, and payment flexibility. However, the increasing use of these services raises the risk of consumptive behavior and a lack of financial control, especially when users lack adequate financial literacy. This condition is exacerbated by the younger generation's trend-following lifestyle and the influence of social media, which encourages impulsive spending patterns. The purpose of this study is to analyze the influence of PayLater services, lifestyle, and financial literacy on financial behavior. The population in this study was 2,036 students, with a purposive sampling technique with a sample of 118 respondents. The types of data were primary and secondary data, the data collection method was a questionnaire, and the analysis method was Partial Last Square (PLS). The results of this study indicate that PayLater services, lifestyle, and financial literacy have a significant influence on financial behavior.